Effect of panelling, application of the Kutta conditio and the way of positioning the control points on the numerical solution of panel methods. Part II - Bahbah, Mohamed M.; Maruszewski, Bogdan (Computer Assisted Methods in Engineering and Science, 2023)
An efficient, accurate, and simple numerical method is necessary for analysis and design of an incompressible potential flow around multi-element airfoils. In this paper, which is the subject of the second part of the study, the mathematical model is built utilizing the local coordinate system, while in the first part of the study [2] only the global coordinate system is used. Mathematical model, by the vortex panel method with the use of the stream function, is written for the analysis of potential flow over multi-element airfoils. The computational model is built for both uniform and linear vortex distributions with utilizing the constant stream function boundary condition. From the fact that any study which does not consider deeply and precisely, all the parameters relevant to the computational model, might make it fragmentary. Hence, the following parameters are tested to investigate their effect on the accuracy of the method. They are: both types of the vortex distribution, two types of panelling, different ways of applying the Kutta condition, and two ways of positioning the control points. For the purpose of easier comparison, the study cases performed using the present model are restricted only to single-element airfoils; NACA 0012 airfoil at an angle of attack a = 8.3°, and a cusped trailing edge 15 percent thick Van de Vooren airfoil at a = 5°.